Gene regulation and epigenetics in Friedreich's ataxia. (17th July 2013) - Yandim, Cihangir; Natisvili, Theona; Festenstein, Richard
Abstract: This is an exciting time in the study of Friedreich's ataxia. Over the last 10 years much progress has been made in uncovering the mechanisms, whereby the Frataxin gene is silenced by (GAA)n repeat expansions and several of the findings are now ripe for testing in the clinic. The discovery that the Frataxin gene is heterochromatinised and that this can be antagonised in vivo has led to the tantalizing possibility that the disease might be amenable to a more radical therapeutic approach involving epigenetic modifiers. Here, we set out to review progress in the understanding of the fundamental mechanisms whereby genes are regulated at this level and how these findings have been applied to achieve a deeper understanding of the dysregulation that occurs as the primary genetic lesion in Friedreich's ataxia.